Homotopy analysis method for thermophoretic particle deposition effect on magnetohydrodynamic mixed convective heat and mass transfer past a porous wedge in the presence of suction - Ismoen, Muhaimin (Maik Nauka-Interperiodica Publishing, Profsoyuznaya Ul 90, Moscow, 117997, Russia, 2010)
Homotopy analysis method is used to analyze the effect of thermophoretic particle deposition on magnetohydrodynamic mixed convection flow with heat and mass transfer over a porous wedge. An explicit analytical solution is obtained which is valid throughout the solution domain and is consistent with numerical results. © 2010 Springer Science+Business Media, Inc.